METODE LIQÃ‚â€™ DAN KASHF DALAM PERIWAYATAN HADIS - Idri, Idri (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2015)
The historical account of hadith literatures clarifies that there are different methods among Muslim scholars in search of the authenticity of hadith. The dispute lies on the variance methods used by hadith and sufi scholars. Sufi scholars tend to have their own methods in establishing the reliability of hadith narration by liqâ? al-Nabî and kashf. This method suggests that Sufiwith high ranking of spiritualitycould meet Prophet directly by dreams. By this way, Sufi scholar might acquire the original Islamic teachings from Prophet, including hadith. In this, they argue for the authenticity of hadiths narrated by such a way. On the other hand, the methods used by sufi are not accommodated by hadith scholars. It is said that every hadith narrated by dream or kashf is unrecognized and considered as false (maw?û?). Addressing these differences, this article tries to examine some problems related to the method of authenticity of hadith narration, the account of hadith on the convergence to the Prophet by dream, kashf as a source of Islamic teaching, the status of mysterious hadiths transmission, and the validation of knowledge based on kashf.